The Effect of Workload on Turnover Intention with Work Stress as a Mediating Variable Among Employees of “Budiman Swalayan” Ulak Karang Padang - Cipa, S.Zilfa Azura; Yuki Fitria, Yuki Fitria (Jurnal Economic Resource, 2025)
The fluctuating employee turnover rates at Budiman Swalayan Ulak Karang from 2022 to 2024 suggest dynamic work conditions that may reflect issues in human resource management. This study aims to analyze the effect of workload on turnover intention with work stress as a mediating variable. Data were collected through questionnaires from 57 permanent employees and analyzed using descriptive statistics and path analysis based on Partial Least Squares (PLS) with SmartPLS 3.0. The results show that workload does not directly affect turnover intention, but significantly influences work stress, which fully mediates the relationship. The findings highlight the importance of managing work stress to reduce turnover intention. This study implies that organizations should prioritize stress-reduction strategies, such as workload balancing and employee support systems, to enhance employee retention. The results also provide practical insights for HR policies aimed at fostering a healthier and more sustainable work environment.